1997
DOI: 10.2307/3433543
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Macrophage Recruitment and Activation in Asbestos-Induced Pleural Injury

Abstract: The pathogenesis of asbestos-induced pleural fibrosis is poorly understood. Moreover, there has been a long-standing controversy regarding the relative potential of different commercial types of asbestos to cause pleural disease. We postulated that inhaled asbestos fibers translocate to the pleural space where they stimulate the recruitment and activation of pleural macrophages. To test this hypothesis, and to determine whether there are differences between inhaled amphibole and serpentine asbestos, Fischer 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 4 publications
(4 reference statements)
2
18
0
Order By: Relevance
“…Macrophages phagocytize asbestos but are unable to ''digest'' these fibers. Possibly because they are damaged by asbestos, these macrophages release TNF-␣ (prevalently) and other cytokines (8,12). TNF-␣ can also be released by HM, for example, when these cells are stimulated with erythromycin (38) or by crocidolite as shown here.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Macrophages phagocytize asbestos but are unable to ''digest'' these fibers. Possibly because they are damaged by asbestos, these macrophages release TNF-␣ (prevalently) and other cytokines (8,12). TNF-␣ can also be released by HM, for example, when these cells are stimulated with erythromycin (38) or by crocidolite as shown here.…”
Section: Discussionmentioning
confidence: 78%
“…In animal models, asbestos induces the expression of monocyte chemoattractant protein-1 by mesothelial cells. Monocyte chemoattractant protein-1 expression favors the macrophage inflammatory response within the pleural space that follows asbestos exposure (12,15). Macrophages phagocytize asbestos but are unable to ''digest'' these fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, MIP1a, secreted from rnTiO 2 burden alveolar macrophages, is possibly involved in the promotion of lung carcinogenesis (Xu et al, 2010). Similarly, pleural macrophage recruitment and activation are involved in the pathogenesis of asbestos (Choe et al, 1997). These results indicate two contrasting roles of alveolar macrophages in pathogenesis and host defense.…”
Section: Discussionmentioning
confidence: 89%
“…As discussed below, there are numerous studies supporting the concept that there is an inflammatory reaction following asbestos exposure (Choe et al, 1997). Hill et al (2003) reported that amosite asbestos causes pleural inflammation by increased secretion of Intercellular Adhesion Molecule-1 (ICAM-1), Monocyte Chemoattractant Protein-1 (MCP-1) and Macrophage Inhibitory Protein-2 (MIP-2) in pleural lavage fluid as well as in vitro mesothelial cell culture (Hill et al, 2003).…”
Section: Introductionmentioning
confidence: 99%